Energy efficiency retrofitting for old buildings in a low-income district of Amman, Jordan - Jamal O. Jaber; Ghazi Marahleh; Suleiman Al-Lubani; Mohammad Khrisat (Academia Green Energy)
This study aimed to contribute to the limited literature on energy efficiency (EE) retrofitting of old buildings, focusing on urban and low-income districts. The case study considered a small zone consisting of approximately 80 old family dwellings in Amman city. The conducted field survey was designed to collect basic data about occupants’ demographics, building conditions, energy consumption, awareness, and willingness to invest in EE measures. A large fraction of residents confirmed that no- or low-cost measures, such as switching off lights and bulb replacement, are already implemented. However, most of them had not even considered investing in EE measures to improve the thermal performance of dwelling envelopes. Equally important, none of the interviewed residents indicated that they would consider replacing old inefficient household appliances in the near future or acquiring new highly efficient machines unless there is direct financial aid or a grant program supported by the government or local authorities to enhance EE. The small fraction of people who showed some understanding of EE remain reluctant to invest in costly items, such as thermal insulation of external walls or replacing windows, most likely due to their very limited financial capability. It is recommended to introduce a tailored scheme to cause a positive shift in current energy consumption behaviors toward more efficient practices, leading to greenhouse gas (GHG) reductions in old residential buildings. This could only be achieved by creating and allocating a special fund to assist poor families in improving EE in their dwellings. Further investigations are highly needed to explore various subjects, including occupant psychological behaviors and responses related to energy use and EE in the residential sector.